2009
DOI: 10.1590/s0100-84042009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de diferentes níveis de enriquecimento por fósforo sobre a estrutura da comunidade perifítica em represa oligotrófica tropical (São Paulo, Brasil)

Abstract: -(Effect of different levels of phosphorus enrichment on periphyton community structure in a tropical oligotrophic reservoir (São Paulo, Brazil)). Nutrient diffusing substrata (NDS) were used to determine the effect of added phosphorus on the periphyton development in a shallow reservoir (Lago do IAG, PEFI, São Paulo). Three treatments (n = 2) were designed: control (without phosphorous addition) and two levels of phosphorus addition (P 1 = 0.1 M and P 2 = 0.5 M KH 2 PO 4 ). NDS surface was covered with a 20 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 52 publications
2
12
1
2
Order By: Relevance
“…The increased periphytic algae diversity and nonoccurrence of competitive exclusion were reported in experiments with P? enrichment (Ferragut and Bicudo 2009). Considering that the periphytic community is primarily limited by P?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased periphytic algae diversity and nonoccurrence of competitive exclusion were reported in experiments with P? enrichment (Ferragut and Bicudo 2009). Considering that the periphytic community is primarily limited by P?…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the periphytic community is primarily limited by P? (Vercellino and Bicudo 2006;Ferragut and Bicudo 2009), increased nutrient availability probably favored limiting the increase in complexity.…”
Section: Discussionmentioning
confidence: 99%
“…palea was one of the taxa abundant in the treatment with N+P addition. In experiment with the addition of nutrients in urban reservoir, Ferragut and Bicudo (2009) found that Nitzschia palea and Monoraphidium arcuatum were the most abundant species in the P treatment, while M. contortum was abundant in the N+P treatment. According to the author, Nitzschia palea was associated with greater phosphorus concentration.…”
Section: Cosmarium Regenesiimentioning
confidence: 99%
“…The structure of the periphytic algae communities can be altered by artificial addition of nutrients (Murakami and Rodrigues, 2009). In addition the species structure (chlorophytes and diatoms) were sensible to phosphorus availability and P-addition (Ferragut and Bicudo, 2009), showing that the phosphorus, especially, may be considered a driver of periphytic algae (Ferragut and Bicudo, 2009;Murakami and Rodrigues, 2009). Preliminary synthesis of the evaluation of nutrient limitation to algal growth reveal phosphorus as the most limiting element in reservoirs (Huszar et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Their establishment in these environments is the outcome of complex interactions between many factors, such as disturbances (Biggs et al, 1998), nutrient availability (Ferragut and Bicudo, 2009;Dunck et al, 2013a), light (Tuji, 2000) and hydrodynamics (Algarte et al, 2009).…”
Section: Introductionmentioning
confidence: 99%